Medication non-adherence and its predictors among patients with bipolar disorder in Northwest Ethiopia - Fasil Bayafers Tamene; Endalamaw Aschale Mihiretie; Tirsit Ketsela Zeleke; Ashenafi Kibret Sendekie; Eyayaw Ashete Belachew; Samuel Agegnew Wondm (Scientific Reports)
Abstract While pharmacotherapy is the primary approach for treating patients with bipolar disorder, non-adherence is the most common barrier preventing these patients from achieving optimal medication effectiveness. This study aimed to assess medication non-adherence and its predictors among patients with bipolar disorder in Northwest Ethiopia. A hospital-based cross-sectional study was conducted among 404 patients with bipolar disorder in Northwest Ethiopia from January to March 2024. Study participants were enrolled using systematic random sampling. Medication non-adherence was measured using the Medication Adherence Rating Scale (MARS). Data were entered and analyzed using Epi-data version 4.6.0 and SPSS version 26, respectively. A multivariable logistic regression model was fitted to identify predictors of medication non-adherence. Variables with a P-value < 0.05 at a 95% confidence interval were considered statistically significant. The prevalence of medication non-adherence was 39.9%. Number of admissions (AOR = 2.83, 95% CI 1.21, 6.59), suicidal attempts (AOR = 2.75, 95% CI 1.14, 6.63), current substance use (AOR = 2.09, 95% CI 1.13, 3.85) and social support (AOR = 3.57, 95% CI 1.08, 11.81) were statistically significant predictors of medication non-adherence. In this study, more than one-third of the respondents were found to be non-adherent. Participants with frequent admissions, suicidal attempts, current substance use and poor social support require prompt screening and critical follow-up to improve medication adherence.